Capacitance-based microfluidic device for early ammonia detection in river water - Muhammad Muhaimin bin Ramli; Mohd Ridzuan bin Ahmad (Institute of Advanced Engineering and Science, 2020)
This paper proposes a design of a microfluidic device for early detection of ammonia in river water based on capacitance measurement. A microfluidic device is designed and simulated to measure the content of ammonia in river water by using the COMSOL finite element analysis (FEA) software. This paper describes the system in detail from the conceptual idea to the hardware implementation. The microfluidic device works by inserting the sample of water into the device to be tested. A pair of electrodes is connected to the electrical circuit and the value of the capacitance of the water sample is measured. The tested samples are normal river water and contaminated river water which have ammonia in it. Several investigations have been done via the simulation, i.e. the size of the electrode, the difference in water flow gap, the distance between the electrode, speed of the water and the capacitance of the water. The results show that the proposed microfluidic design is capable to detect ammonia inside river water under 2 ppm concentration.